LOCATION HOUSING AFFORDABILITY INDEX: ANALYSING THE RELATIONSHIPS - Hassan, Mohd Azren; Abdullah, Yusfida Ayu; Omar, Dasimah; Danial, Muhammad Hakim (PLANNING MALAYSIA, 2021)
Previous studies claimed that Malaysia is inclined towards a severely unaffordable housing price. Despite such crucial studies, the topics do not provide sufficient empirical evidence to establish a relationship between housing prices, housing and transportation expenditure in Malaysia. Therefore, this study examines the role of these variables in determining the Location Housing Affordability Index. The research had therefore identified measurement items that contribute to Location Housing Affordability Index. The primary data was obtained from urban areas in the Klang Valley using questionnaires, where a total of 363 respondents were selected using the Simple Random Sampling technique. The Partial Least Squares (PLS) method was adopted in analysing the collected data to determine the relationship. The outcome demonstrated the relationship between housing price, housing and transportation expenditure, indicating the significance of the Location Housing Affordability Index and can be a reference for housing policymakers.